Habit persistence in tourist sub-industries - Adrian R. Fleissig (Journal of Applied Economics, 2021)
Habit persistence across six U.S. tourism sub-industries is estimated using a dynamic forward looking model. Estimates show that habits largely determine current expenditure for air transportation, shopping, accommodation, and other transportation. Estimated uncompensated price elasticities find that air transport and accommodation are price elastic in the short-run and long-run. Shopping is price inelastic in the short-run but price elastic in the long-run. An important result is that air transportation and other transportation are elastic substitutes for price changes in air transportation but inelastic substitutes for price changes in other related transportation. Estimates show that expenditure across most of the tourist sub-industries is closely related because they are gross complements. Food and beverages are necessities, price inelastic, and relatively unresponsive to changes in expenditure across the sub-industries. The estimates show that policy makers and tourist marketing should account for habit persistence and differences between the short-run and long-run.
Keywords: 330; Habit formation; short-run and long run estimates; tourist sub-industries